A time-expanded network reduction matheuristic for the logistics service network design problem. (March 2021) - Belieres, Simon; Hewitt, Mike; Jozefowiez, Nicolas; Semet, Frédéric
Highlights: We consider a logistics service network design problem encountered by third-party logistics. We propose a matheuristic based on the dynamic discretization discovery method. Our approach provides high-quality solutions in reasonable time and outperforms a commercial solver. Case study on real-world instances provides insights into how the distribution strategy influences the overall logistics cost. Abstract: Planning cost-effective logistics operations involve the integration of multiple decision-making levels. In the domain of supply chain management, the last decades have seen the emergence of 3PL service providers that specialize in integrating warehousing and transportation services. In this paper, we study the operations performed by a 3PL service provider in the supply chain management of a French restaurant chain. The transportation planning process is assisted by solving the Logistics Service Network Design Problem (LSNDP). As realistic instances are too large for on-the-shelf optimization solvers to solve in acceptable run-times, we develop a network reduction heuristic inspired by the recent Dynamic Discretization Discovery algorithm. Through an extensive series of experiments carried out on instances based on the operations of an industrial partner, we demonstrate the efficiency of the proposed approach. We also investigate the impact of the distribution strategy used in practice to determine the transportation plan and how this distribution strategy can be modified to reduce the overall logistics costs.